Salivary nicotine and cotinine concentrations in unstimulated and stimulated saliva - Robson, Noor Zurani; Bond, A.J.; Wolff, K. (Academic Journals, 2010)
Salivary nicotine and salivary cotinine is widely used in clinical and epidemiological studies to validate smoking cessation. However, the reported collection for salivary nicotine and salivary cotinine vary by technique and duration. This study investigated the influence of salivary collection by unstimulation and stimulation technique of the concentration of salivary nicotine and salivary cotinine. It was found that unstimulated technique produced the highest salivary nicotine concentration, whereas stimulated technique produced the highest salivary cotinine concentration. The results of this study suggest that it is important to standardise salivary nicotine and cotinine collection technique.